2021
DOI: 10.1101/2021.02.13.431098
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Attention to speech: Mapping distributed and selective attention systems

Abstract: Daily life is full of situations where many people converse at the same time. Under these noisy circumstances, individuals can employ different listening strategies to deal with the abundance of sounds around them. In this fMRI study we investigated how applying two different listening strategies, Selective vs. Distributed attention, affects the pattern of neural activity. Specifically, in a simulated cocktail party paradigm, we compared brain activation patterns when listeners attend selectively to only one s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…34 In contrast, functional magnetic resonance imaging (fMRI) offers comparatively good spatial discrimination ability. Such studies have shown that selective attention to cocktail-party speech does not only modulate information processing in low-level auditory regions but also in extensive superior temporal, inferior parietal and inferior frontal brain regions (e.g., 23,[35][36][37][38][39] ). Furthermore, multivariate pattern analyses on cocktail party fMRI data have indicated that neuronal populations that show differential responses during selective attention to speech are observed relatively globally in disparate cortical regions.…”
Section: Introductionmentioning
confidence: 99%
“…34 In contrast, functional magnetic resonance imaging (fMRI) offers comparatively good spatial discrimination ability. Such studies have shown that selective attention to cocktail-party speech does not only modulate information processing in low-level auditory regions but also in extensive superior temporal, inferior parietal and inferior frontal brain regions (e.g., 23,[35][36][37][38][39] ). Furthermore, multivariate pattern analyses on cocktail party fMRI data have indicated that neuronal populations that show differential responses during selective attention to speech are observed relatively globally in disparate cortical regions.…”
Section: Introductionmentioning
confidence: 99%